2013
DOI: 10.1002/jbm.a.34822
|View full text |Cite
|
Sign up to set email alerts
|

Impact through time of different sized titanium dioxide particles on biochemical and histopathological parameters

Abstract: Due to corrosion, a titanium implant surface can be a potential source for the release of micro (MPs) and nano-sized particles (NPs) into the biological environment. This work sought to evaluate the biokinetics of different sized titanium dioxide particles (TiO2 ) and their potential to cause cell damage. Wistar rats were intraperitoneally injected with 150 nm, 10 nm, or 5nm TiO2 particles. The presence of TiO2 particles was evaluated in histologic sections of the liver, lung, and kidney and in blood cells at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 56 publications
3
34
0
1
Order By: Relevance
“…Despite the kidney being exposed to the effect of NPs during ultrafiltration, the impact of NPs on the kidneys remains to be clarified (3). In previous work we also encountered deposits of NPs in the kidney, although they did not cause histological alterations (23). Nevertheless, some studies found NPs to cause glomerular edema and accumulation of protein in renal tubules, as a consequence of retention of TiO 2 particles (43).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Despite the kidney being exposed to the effect of NPs during ultrafiltration, the impact of NPs on the kidneys remains to be clarified (3). In previous work we also encountered deposits of NPs in the kidney, although they did not cause histological alterations (23). Nevertheless, some studies found NPs to cause glomerular edema and accumulation of protein in renal tubules, as a consequence of retention of TiO 2 particles (43).…”
Section: Discussionmentioning
confidence: 76%
“…Corrosion/tribocorrosion is not only a local problem because the particles released during the process can migrate to distant sites . In this regard, previous work conducted at our laboratory , using rats injected i.p. with 150, 10, or 5 nm APS TiO 2 particles showed the presence of foci of necrosis in liver sections at 3 and 12 months only in rats injected with 10 and 5 nm APS particles.…”
Section: Discussionmentioning
confidence: 99%
“…Anyway, further studies need to be done until the accuracy of this hypothesis is proved. [16] Bruno et al [17] hypothesized that due to corrosion, the dental titanium implant's surface can be a potential source of the release of microsized particles (MPs) and nanosized particles (NPs) into the body's biological environment. This work sought to evaluate the biokinetics of different sized titanium dioxide particles (TiO 2 ) and their potential to cause organ's cell damage.…”
Section: Resultsmentioning
confidence: 99%
“…This is why, the implementation of more clinical and laboratory studies for the detection of any adverse effects of titanium's particles on the body's cells is highly suggested. [17] Royhman et al [18] evaluated the corrosion effect of nicotine on Ti-6Al-4V under physiological conditions. It was hypothesized that nicotine in artificial saliva would have an adverse side effect on the corrosion of Ti-6Al-4V.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, metallic titanium implants are a potential source of release of titanium dioxide (TiO 2 ) microparticles (MPs) and nanoparticles (NPs) into the bioenvironment . It is well known that NPs have a greater surface‐to‐volume ratio than MPs, and are therefore biologically more reactive and potentially more harmful to human health …”
Section: Introductionmentioning
confidence: 99%